Biopesticide Application Of Bacillus thuringiensis Local Isolate To Control Atherigona exigua Pest On Corn Plants - Christina Leta Salaki; Jackson Watung (Sam Ratulangi University, 2022)
Atherigona exigua is one of the main plant pest organisms (OPT) in maize. Among these pest control alternatives, the use of Bacillus thuringiensis bacteria has received attention because of its efficiency and low impact on natural enemies. This study aims: (1) to obtain the concentration of B. thuringiensis which has a high killing power on mortality of A. exigua larvae, (2) to determine the pathogenicity of B. thuringiensis to A. exigua. Testing for killing power and pathogenicity used the